2015
DOI: 10.1039/c5ra19114a
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence enhancement from silicon quantum dots located in the vicinity of a monolayer of gold nanoparticles

Abstract: There is an optimum separation distance between light-emitting silicon quantum dots and a monolayer of nearly spherical gold nanoparticles to achieve a photoluminescence enhancement from the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…In a previous work [24], we found that the plasmon resonances of several sets of gold nanoparticles randomly distributed are always at the same location in a UV-Vis absorbance spectrum, if the nanometric configurations of the depositions are very similar (average particle size, particle shape, and particle density). Therefore, in this work we carried out a systematic characterization of our highly reproducible set of Al-NPs deposited over the surface of the previously mentioned substrates by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), we prove that growth characteristics remain the same for all substrates.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a previous work [24], we found that the plasmon resonances of several sets of gold nanoparticles randomly distributed are always at the same location in a UV-Vis absorbance spectrum, if the nanometric configurations of the depositions are very similar (average particle size, particle shape, and particle density). Therefore, in this work we carried out a systematic characterization of our highly reproducible set of Al-NPs deposited over the surface of the previously mentioned substrates by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), we prove that growth characteristics remain the same for all substrates.…”
Section: Introductionmentioning
confidence: 77%
“…We carried out a visual inspection and optical microscopy analysis of each exploratory deposition. An SCN on quartz must be imperceptible to the naked eye, while at 1000× in an optical microscope it is possible to identify a very slight change in hue on the quartz surface (increasing in turbidity) [24]. When these two qualitative characteristics were observed, we proceeded to stage III.…”
Section: Stage IImentioning
confidence: 99%
“…The gold nanoparticles (AuNPs) and silicon quantum dots (SiQDs) thin films were obtained using deposition conditions previously studied, which gave rise to average particle sizes of 2.9 nm and 3.1 nm, respectively [ 11 , 19 ]. It can be observed in both samples from HRTEM images ( Figure 3 a,b) a uniform distribution of particles throughout the whole surface and quasi-spherical shape.…”
Section: Resultsmentioning
confidence: 99%
“…Those enhancements are reported at emission frequencies that correspond to the collective dipole plasmon resonances [ 15 , 16 , 17 , 18 ]. In this regard, we recently reported photoluminescence (PL) enhancement from thin films of SiQDs embedded in silicon nitride coupled to a monolayer of Au nanoparticles which are separated by a nanometric dielectric silicon nitride thin film [ 19 ]. In that article, the films were deposited using dry and low-temperature techniques highly compatible with the pre-existing silicon microelectronics technology, such as remote plasma enhanced chemical vapor deposition (RPECVD) and direct current (DC) sputtering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation